Measurement and characterization of distinctive clinical phenotypes using the Frontotemporal Lobar Degeneration Module (FTLD‐MOD). Issue 6 (13th May 2020) - Gefen, Tamar; Teylan, Merilee A.; Besser, Lilah; Pollner, Emma; Moshkovich, Anna; Weintraub, Sandra
Abstract: Introduction: The Frontotemporal Lobar Degeneration Module (FTLD‐MOD) was designed as a research neuropsychological battery to evaluate clinical symptoms associated with FTLD. This study investigated whether the FTLD‐MOD could differentiate between primary progressive aphasia (PPA) and behavioral variant frontotemporal dementia (bvFTD), two distinct FTLD‐related syndromes. Methods: Retrospective analysis was conducted on data collected from the initial visit of 165 subjects with PPA, 268 with bvFTD, and 251 cognitively normal controls from the National Alzheimer's Coordinating Center. Generalized linear models were used to compare group performance patterns on FTLD‐MOD tasks of language, behavior, and memory. Results: PPA participants showed significantly poorer performances on all language tasks whereas bvFTD participants demonstrated poorer performances on most behavioral measures. There were no differences in memory performances. Descriptive data on participant groups are provided for reference. Discussion: Findings from this multi‐center sample suggest that the FTLD‐MOD can differentiate between distinctive clinical phenotypes commonly associated with FTLD.